The Evaluation of Antibacterial Coatings Against Commonly Found Pathogenic Bacteria in the Environment—Implications for Environmental Safety and Infection Prevention - Wei-Chuan Chen; Mei-Hsiu Ho; Shin-Huan Yuan; Hui-Wen Chou; Chi-Chuan Chang; Chih-Hung Chen; Yusen Eason Lin (Pathogens)
Microorganisms, including pathogens that cause skin, respiratory, and urinary tract infections, are widespread in our environment. Despite routine cleaning with bleach and disinfectants, the transmission of pathogens still occurs, leading to potential infectious diseases. This study aimed to determine the antibacterial effect of two coating formulas against common environmental pathogens like Escherichia coli, Staphylococcus aureus, Acinetobacter baumannii, Pseudomonas aeruginosa, Salmonella sp., vancomycin-resistant Enterococcus faecium, and Klebsiella pneumoniae. The antibacterial coatings exhibited efficacy against these pathogens, with a bacterial reduction rate (R) greater than two, even after prolonged bleach cleaning. However, UV exposure may affect the efficacy of such coatings. The antibacterial coatings can eliminate the need for repetitive consumption of toxic detergents and reduce cleaning manpower, making them an environmentally friendly product for safety control and infection prevention.